Дисконтирование денежных потоков коммерческого банка - Проказа, Т.В. (Економіка промисловості, 2012)
Запропоновано метод дисконтування грошового потоку для власного капіталу як найбільш прийнятний для оцінки вартості банку, оскільки включає рух фінансових ресурсів від основної діяльності та вхідні й вихідні потоки комерційного банку. Обґрунтовано доцільність модифікації формули грошового потоку для власного капіталу.
Ключові слова: дисконтування грошового потоку, оцінка вартості бізнесу, формула грошового потоку. Предложен метод дисконтирования денежного потока для собственного капитала как наиболее приемлемый для оценки стоимости банка, поскольку включает движение финансовых ресурсов от основной деятельности и входные и выходные потоки коммерческого банка. Обоснована целесообразность модификации формулы денежного потока для собственного капитала.
Ключевые слова: дисконтирование денежного потока, оценка стоимости бизнеса, формула денежного потока. The Ukrainian economy will not be able to take a worthy place in the world’s economic space without the solution of problems concerning effective industrial production development. Functioning in the framework of the state industrial policy, industrial city has to be given certain economic levers and financial resources to address its own problems at the local level. One of the most powerful economic levers is taxation, which at the city level is represented by an institute of local taxation. The hypothesis of the research is that in an industrial city, which has its peculiar problems and features of development, it is possible to achieve an increase in tax revenues and economic growth in a certain time interval at the expense of tax policy changes at the local level. Taking into account the hypothesis of the research, considering existing city models and institutional peculiarities of Ukraine, a system-dynamic model of industrial city development under the influence of local taxation is proposed, developed in the framework of neoclassical economic theory. The modeling object is industrial Donetsk city. The model includes industrial city problems such as the shortage of investment resources, that has a negative influence on availability of fixed assets, and through them to production output, as well as environment in the form of pollutant emissions into atmospheric air, which has a direct negative impact on the health status of population, life expectancy, and therefore human capital as a factor of economic growth. Three taxes are suggested forming the local taxation system: industrial enterprises income tax, environmental tax on pollutant emissions into atmospheric air from stationary sources of pollution, and personal income tax. The results of economic-mathematical modeling confirm the fact that the presence of significant tax levers at the local level and the possibility of their application for regulation of economic development contribute to the growth of socio-economic indicators of the city.
Keywords: local taxation, city development model, industrial city